Late antique studies in memory of Alan Cameron (Leiden ; Boston)
xxxii, 321 sayfa
Keywords: “The classicist and historian Alan Cameron (1938-2017) was, among other achievements, one of the scholars who most contributed to the refoundation of late-antique studies. In this tribute W. V. Harris and Anne Hunnell Chen have brought together fourteen contributions that cover a broad range of historical, literary, and art-historical topics, running from the first century AD to the ninth. Some contributions concern Cameron's own favourite themes (the Greek Anthology, the Historia Augusta, circus factions, the transmission of texts), while others seek to assess his work and its impact. Other papers branch out from his concerns to discuss slavery, simony, and hospitals. Fourth- and fifth-century writers are often to the fore and the volume includes a new text by the poet Dioscoros of Aphrodite.“ --